2022
DOI: 10.3390/agriculture12030326
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Low Copper-Containing Chemicals against Olive Leaf Spot Disease Caused by Venturia oleaginea

Abstract: The high level of copper (Cu) accumulation in the soil, the risk of surface water contamination, and the potential public health problems due to Cu entering the food chain have raised concerns on the use of Cu compounds in agriculture, including olive growing. As a consequence, there is worldwide regulatory pressure on agricultural systems to limit the use of Cu compounds. Hence, a field trial was carried out to evaluate the effectiveness of low copper containing chemicals to control olive leaf spot (OLS) dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
2
6
1
Order By: Relevance
“…In other field studies, the use of dodine and copper oxychloride showed similar effects ( Iannotta et al., 2002 ; Belfiore et al., 2014 ; Adawi et al., 2022 ). The differences in the results obtained in the present study with respect to those of Iannotta et al.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In other field studies, the use of dodine and copper oxychloride showed similar effects ( Iannotta et al., 2002 ; Belfiore et al., 2014 ; Adawi et al., 2022 ). The differences in the results obtained in the present study with respect to those of Iannotta et al.…”
Section: Discussionsupporting
confidence: 59%
“…In other field studies, the use of dodine and copper oxychloride showed similar effects (Iannotta et al, 2002;Belfiore et al, 2014;Adawi et al, 2022). The differences in the results obtained in the present study with respect to those of Iannotta et al (2002) and Belfiore et al (2014) may be due to the heavy but still mainly asymptomatic attack of the trees in our study.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…Interesting results have been recently obtained with a new formulation containing copper complexed with gluconate and lignosulphonate (Disper Cu Max ® -Eden Modern Agriculture S.L-Spain), which, in spite of the lower content of metallic copper (e.g. five times lower than copper hydroxide), proved more effective than traditional formulations (Almadi et al., unpublished; Adawi et al., 2022 ). The higher efficacy was associated to a supposed cytotropic phytomobility of the formulation, which may also exert a curative action.…”
Section: Controlmentioning
confidence: 99%
“…In pot-cultivated olive plants, promising results were obtained with a number of plant resistance inducers, applied as foliar spray or soil drench: acibenzolar-S-methyl, 3-amino butyric acid, chitosan, harpin, laminarin, phosphates (FoliR-Fos 400 ® ), salicylic acid and silicon (Actisil ® ) ( Obanor et al., 2013 ; Nascimento-Silva et al., 2019 ; Tziros et al., 2021 ). Recently, in an open-field trial, a very good protection against V. oleaginea attacks, comparable to the dodine, was demonstrated using the self-defense inducer Disper Broton GS ® ( Adawi et al., 2022 ). This formulation also contains complexed copper with an amount of metallic copper 10 times lower than copper hydroxide.…”
Section: Controlmentioning
confidence: 99%